Long-term restoration of alpha-L-iduronidase activity in fibroblasts from patients with mucopolysaccharidosis type I after non-viral gene transfer - Poswar, Fabiano de Oliveira; Mayer, Fabiana Quoos; Burin, Maira Graeff; Matte, Ursula da Silveira; Giugliani, Roberto; Baldo, Guilherme (Clinical and Biomedical Research, 2017)
Mucopolysaccharidosis type I (MPS I) is a lysosomal storage disorder due to deficiency of alpha-L-iduronidase (IDUA). Limitations such as need of weekly injection, high morbidity and mortality and high cost of the current treatments show the need for new approaches to treat this disease. In this work we aimed to correct fibroblasts from a MPS I patient using non-viral gene therapy. Using a plasmid encoding the human IDUA cDNA, we achieved stable high IDUA levels in transfected fibroblasts up to 6 months of treatment. These results serve as proof-of concept that a non-viral approach can correct the enzyme deficiency in cells from lysosomal storage disorders patients, which can be used as a tool for research a series of disease aspects. Future studies will focus on verify if this approach can be useful in small animals and clinical trials.